A study of Corporate Social Reporting (CSR) on occupational safety and health in Malaysia / Azlina Rahim, Zaharah Abdullah and Zaleha Mahat - Rahim, Azlina; Abdullah, Zaharah; Mahat, Zaleha (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
This study examines the disclosure of Occupational Safety and Health (OSH) in the annual reports of trading, plantation and industry companies listed on the Main Board of Bursa Malaysia. The relevant data were obtained through analysis of annual reports in the Bursa Malaysia library for the year 2003. Out of 304 companies, 44 percent from Trading, 15 percent from Plantation and 41 percent from the Industrial Product sector disclosed OSH information. Most of the companies disclosed the information in a separate section (54 percent) while others in chairman statement (21 percent), stand-alone report (8 percent), operational review (11 percent),dairy or calendar (2 percent) and 4 percent in other section. The most popular aspect of disclosure was workplace safety and health management. This study suggests that, companies disclose the information because they like to demonstrate their commitment in managing and improving OSH within the organization. On the other hand, some of the companies did not disclose because there is no requirement by the Bursa Malaysia or Securities Commission to disclose such information.